Identification of glycoside hydrolase CAZymes in rhizospheric soil microbiome of the wild plant species Moringa oleifera - Mohammed Y Refai (Environmental Research Communications)
This study aimed to identify genes encoding glycoside hydrolase (GH) CAZymes in the rhizosphere microbiome of Moringa oleifera using a gene-based approach. By analyzing rhizosphere and bulk soil samples through whole metagenomic shotgun sequencing, distinct gene catalogs were compiled, including classifications from the CAZy database. Bioinformatics tools validated and processed the sequencing datasets. Based on gene abundance, nine GH families were highly prevalent in rhizosphere soil, primarily associated with bacterial phyla Actinobacteria, Bacteroidetes, and Proteobacteria, and genera such as Microvirga, Streptomyces, Sphingomonas, Niastella, Massilia , and Blastococcus . These CAZymes participate in five metabolic pathway subcategories, playing a crucial role in plant stress resistance by producing protective compounds such as ceramide, coumarin, and monolignol alcohols. Several enzymes in KEGG pathways promote glucose synthesis, providing an alternative energy source to photosynthesis and preventing the adverse effects of glucose deprivation. Increased glucose levels enhance nitrogen metabolism and maximize root biomass, morphology, and vitality. In turn, plant-exuded glucose acts as a chemoattractant for beneficial bacteria, particularly Bacillus subtilis , fostering plant-microbe interactions essential for soil health and plant growth. Additionally, N-Glycan assembly-related enzymes were abundant in rhizosphere soil, influencing protein folding, membrane integrity, and bacterial cell surface function, further contributing to microbial adaptation and plant-microbe symbiosis. This study highlights the critical role of GH CAZymes in nutrient cycling, soil fertility, and organic matter decomposition. These enzymes facilitate microbial interactions that improve soil structure and promote carbon sequestration, thereby enhancing biodiversity and supporting sustainable agricultural practices amid climate change. Understanding the functions of rhizosphere CAZymes may offer valuable insights for biotechnological applications in agriculture, particularly in developing biofertilizers or microbial inoculants. Our findings suggest that harnessing beneficial rhizosphere bacteria could provide substantial industrial and agricultural benefits, particularly in enhancing plant resilience and productivity in natural and managed ecosystems.